The Legal Analysis of Defamation Crimes in Family Through The Social Media - Agung, Dirga; Andi Dewi Pratiwi (Alauddin Law Development Journal, 2024)
The right to communicate and obtain information has been regulated in Article 28F of the 1945 Constitution of the Republic of Indonesia. However, the use of social media must still recognize the limits in its use so as not to harm oneself or others, including family. This problem is focused on the problem of defamation that can be ensnared in social media and the limits in expressing opinions. The method used is normative research. The findings of the study indicate that it is necessary to increase awareness in expressing opinions so as not to become shackles. This study concludes that there are limits that need to be known in giving opinions, namely not to insult morals and decency. As well as a legal analysis of criminal acts of insult committed in a closed space.